2017
DOI: 10.1007/s00415-017-8654-1
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of gait in Parkinson’s disease: gray and white matter abnormalities

Abstract: Freezing of gait (FOG) is a disabling disorder that often affects Parkinson's disease (PD) patients in advanced stages of the disease. To study structural gray matter (GM) and white matter (WM) changes in PD patients with and without FOG, twenty-one PD patients with FOG (PD-FOG), 16 PD patients without FOG (PD-nFOG) and 19 healthy subjects (HS) underwent a standardized MRI protocol. For the gray matter evaluation, cortical volume (CV), cortical thickness (CTh), and surface area (SA) were analyzed using the Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 48 publications
6
55
0
Order By: Relevance
“…In our study, we also found obvious significance in two regions. Pietracupa et al 27 also observed a significant decline in superior frontal and precuneus in Parkinson's disease, which was also found in our study. Thus, it is also necessary to consider various factors in the diagnosis of neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we also found obvious significance in two regions. Pietracupa et al 27 also observed a significant decline in superior frontal and precuneus in Parkinson's disease, which was also found in our study. Thus, it is also necessary to consider various factors in the diagnosis of neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 91%
“…A few studies revealed significant correlations between DTI changes and severities in terms of freezing of gait (17,40), risk of falling (16), severity of postural instability and gait disturbance (PIGD) symptoms (18), motor speed and balance (19), and the degree of tremor (41,42). Some studies, using DTI for classifying PD motor subtypes (73,95), have found differentiable group effects only, but no substantial clinical correlations were observed in patients. The abnormal DTI changes in specific regions are considered useful biomarkers that characterize PD symptomology or differentiate PD phenotypes, and thus may provide an enormous potential for managing treatment directions of PD.…”
Section: Dti Correlates Of Motor Dysfunctionmentioning
confidence: 99%
“…A pattern of GM changes has been suggested to occur in the mesial frontal cortex in PD patients with FOG. Pietracupa et al (2017) found that PD patients with FOG exhibit significant changes in WM and cortical thinning of the mesial surface of the bilateral cerebral hemispheres. Vastik et al (2017) found that FOG was associated with regional GM atrophy in the mesial frontal and cingulate cortices.…”
Section: Discussionmentioning
confidence: 91%